(untitled) (Journal of Parents and Teachers, 2026)
This article analyses the relationship between family and school through the lens of pupils’ homework. Homework reflects family involvement in education, and its completion and effectiveness depend on the support of parents, siblings or private tutors. The article shows how homework has a direct influence on the organisation of the home and on parent-child relationships.